Green Economy and Meat Processing–Future Prospects. Issue 1 (October 2021) - Petrovic, Z; Milicevic, D; Vranic, D; Rajic, S; Simunovic, S
Abstract: This paper provides a brief overview of the possible strategies for reducing hydrocarbon emissions from the meat industry according to the Green Deal program of the EU in the next decades. An overview of emerging technologies (h igh-pressure processing (HPP), shock wave technology (SW), ohmic heating (OH) and p ulsed electric field (PEF), cultured meat) that should reduce gas emissions is given, as well as methodologies that can be applied (labelling, sustainable cooking, product lifecycle management (PLM) and product data management (PDM) applications). Noticeably, most novel strategies draw the conclusion that we should go for lower consumption of meat, especially beef, and change habits to eat and prepare foods in energy and environmentally friendly ways, as well as apply the so-called "green" food declaration in the future. Transforming into a climate-friendly economy, protecting biodiversity, and reorienting the agri-food industry growth can contribute to creating greater resilience of society.